The effects of water supply on the physiological traits and yield of tomato - Andryei, Bulgan; Horváth, Kitti Zsuzsanna; Nemeskéri, Eszter (Acta Agraria Debreceniensis, 2019)
The SPAD value, the chlorophyll fluorescence and the canopy temperature of the leaves and fruits of tomato hybrid “H1015” were investigated under non-irrigated (I0), deficit irrigated (I50) and well-irrigated (I100) conditions. The aim of the experiments was to show which treatment effect on the examined traits affected photosynthesis, leaf temperature and yield quantity, as well as quality under water scarcity. In the control treatment (I0), the canopy temperature increased, but the SPAD decreased compared to the other two treatments (I50 and I100). Chlorophyll fluorescence produced a fluctuating result. In the end, the number of the fruits was high, but the number of the sick and green berries was increased.